2015
DOI: 10.1007/s40617-014-0034-z
|View full text |Cite
|
Sign up to set email alerts
|

Applied Behavior Analysis and the Autism Diagnostic Observation Schedule (ADOS): a Symbiotic Relationship for Advancements in Services for Individuals with Autism Spectrum Disorders (ASDs)

Abstract: The Autism Diagnostic Observation Schedule (ADOS) is a widely used diagnostic tool for the assessment of autism spectrum disorders. We compared interobserver reliability scores for observers using the existing guidelines for administration of the ADOS with those of the same observers using modified guidelines that included operational definitions for each area of observation. The results indicated increased mean interobserver reliability scores from 55.83 % using the existing guidelines to 84 % when using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In such assessments [7] the aim is to capture important behavioural cues such as shared mutual attention, imitating other's actions, etc. Such play interactions are also analysed for screening and diagnostics [8] purposes and for longitudinal impact assessments [9] of the selected intervention therapy.…”
Section: Related Workmentioning
confidence: 99%
“…In such assessments [7] the aim is to capture important behavioural cues such as shared mutual attention, imitating other's actions, etc. Such play interactions are also analysed for screening and diagnostics [8] purposes and for longitudinal impact assessments [9] of the selected intervention therapy.…”
Section: Related Workmentioning
confidence: 99%
“…Recent research has focused on providing operational definitions for codes on the ADOS that use language such as, "rarely," "occasionally" or "largely consists of." Guercio and Hahs (2014) found that after providing more precise definitions that included the number of behaviors the child emitted instead of more vague definitions (e.g., replacing "uses poorly modulated eye contact to initiate, terminate or regulate social interaction" with "uses eye contact in durations of less than 2s each to initiate, terminate or regulate social interaction during 70% of the session"), coder provided more accurate scores of the child's behavior and interobserver reliability increased. One benefit of the social approach coding scheme described in this study is that it requires less intensive training than the standard ADOS coding.…”
Section: Discussion Study 1: Reliability and Validitymentioning
confidence: 99%